Transcriptome analysis revealed that ischemic post-conditioning suppressed the expression of inflammatory genes in lung ischemia-reperfusion injury - Liangen Lin; Congcong Sun; Yuanwen Ye; Peng Zhu; Keyue Pan; Linglong Chen (Frontiers in Genetics)
IntroductionIschemic post-conditioning (I-post C) is a recognized therapeutic strategy for lung ischemia/reperfusion injury (LIRI). However, the specific mechanisms underlying the lung protection conferred by I-post C remain unclear. This study aimed to investigate the protective mechanisms and potential molecular regulatory networks of I-post C on lung tissue.MethodsTranscriptome analysis was performed on rat lung tissues obtained from Sham, ischemia-reperfusion (IR), and I-post C groups using RNA-seq to identify differentially expressed genes (DEGs). Subsequently, gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and gene set enrichment analysis (GSEA) were conducted to elucidate significantly enriched pathways in the IR and I-post C groups. Additionally, protein-protein interaction (PPI) network analysis was carried out to examine associations among the DEGs. Pathological changes in lung tissues were assessed using hematoxylin-eosin (H&E) staining. The expression levels of CXCL1 and CXCL6 in the IR and I-post C groups were evaluated through immunofluorescence and Western blotting.ResultsOur results showed that I-post C significantly attenuated both pulmonary edema and inflammatory cell infiltration. Transcriptome analysis identified 38 DEGs in the I-post C group compared to the IR group, comprising 21 upregulated and 17 downregulated genes. Among these, seven inflammation-related DEGs exhibited co-expression patterns with the Sham and IR groups, with notable downregulation of Cxcl1 and Cxcl6. GO analysis primarily linked these DEGs to neutrophil activation, chemotaxis, cytokine activity, and CCR chemokine receptor binding. KEGG analysis revealed enriched pathways, including the IL-17, TNF, and NF-κB signaling pathways. GSEA indicated downregulation of neutrophil chemotaxis and the IL-17 signaling pathway, correlating with reduced expression of Cxcl1 and Cxcl6. Validation of Cxcl1 and Cxcl6 mRNA expression via immunofluorescence and Western blotting supported the RNA-seq findings. Furthermore, a PPI network was constructed to elucidate interactions among the 29 DEGs.ConclusionsThrough RNA-Seq analysis, we concluded that I-post C may reduce inflammation and suppress the IL-17 signaling pathway, thereby protecting against lung damage caused by LIRI, potentially involving neutrophil extracellular traps.